Anticoagulation management: An interdisciplinary curriculum for family medicine residents - Nijjar, Jaspreet; Marr, Patricia; Toubassi, Diana; Kwan, Debora; Papoushek, Christine (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Implication Statement

(untitled)
Énoncé des implications de la recherche